Bio rational green approaches for effective management of post flowering stalk rot in maize (Zea mays) - YADAV, KALPANA; SHARMA, S S; DAHIMA, VINITA; KHOKHAR, M K (The Indian Journal of Agricultural Sciences, 2023)
Present study was carried out to assess efficacy of bio agents and organic ITK’s against post flowering stalk rot at Maharana Pratap University of Agriculture and Technology, Udaipur, Rajasthan during 2019–20. The results of in vitro studies revealed that Trichoderma viride (65%) significantly inhibited the mycelium growth of Fusarium verticillioides. In field conditions, T. viride showed low disease rating 3.0, low per cent disease incidence (25.20%) and high efficacy of disease control (62.27%) with good grain yield 1191 g/plot against the pathogen at 2% concentrations. Maize growers can protect their crop from this disease by using the sustainable, environmentally friendly disease control strategies that were found in our study.